Measuring the effectiveness of spending policy on some macroeconomic variables in Iraq (Journal of Humanities and Social Sciences Research, 2023)
The importance of the spending policy emerges as it is considered one of the most effective financial and economic policies used to influence many critical economic variables, which are classified within the economic planning tools in order to influence the overall economic activity and then reach economic development and overcome and confront the obstacles represented by economic fluctuations by influencing the most important macroeconomic variables. The research aims to verify the effectiveness of the spending policy by measuring its impact on some macroeconomic variables in Iraq using Markov models with variable systems, which show effectiveness during booms and busts. In order to increase global demand, the volume of public spending in Iraq increased. Still, it was not effective in terms of affecting the domestic product because of the contribution of oil revenues at the time to the formation of the gross domestic product, and it caused a rise in inflation rates. However, monetary policy intervened through its tools, which led to relative stability in the general level of prices on an extended basis in the short and long term. The research also suggested intensifying the government's efforts to prioritize and adjust its spending policies by reforming its structure and its various aspects, with the need to improve and achieve high efficiency in directing that policy in line with the diversification of its financing sources to reach the desired economic goals.